Nursing considerations for patients undergoing robotic-arm assisted joint replacements. (27th May 2021) - Asokan, Ajay; Baawa-Ameyaw, Joanna; Kayani, Babar; Radhakrishnan, Ganan T; Magan, Ahmed A; Haddad, Fares S
Abstract : Robotic-arm assisted arthroplasty (RAA) has gained popularity over the past decade because of its ability to provide more accurate implant positioning with less surgical trauma than conventional manual arthroplasty. It has shown better early functional outcomes, less postoperative pain and shorter inpatient stays. A multidisciplinary approach is crucial in improving overall outcomes and ensuring this technology is implemented efficiently and safely, but there is limited published literature on the nursing considerations for managing patients undergoing RAA. This article aims to provide a pragmatic approach for nursing care in the pre-, intra-, and postoperative phases of RAA.